NURSING SKILL MANAGEMENT IN IMPLEMENTING TRIAGE IN THE EMERGENCY DEPARTEMENT - Ilhamsyah; Aprilia, Arlena Dwi Suci; Adhiwijaya, Ardian (Homes Journal: Hospital Management Studies Journal, 2025)
Backround: One of the services available in the emergency installation is triage. Triage is an action for patients who will enter the emergency department (ED) selected based on their emergency. Through the implementation of triage, patient satisfaction in the Hospital can be achieved and death and disability in emergency cases can be minimized, so it is very important for nurses to have knowledge and skills in implementing triage. Objective: The purpose of this study was to determine the relationship between knowledge and nurse skills in implementing triage in the emergency room (ER) of Labuang Baji Hospital, Makassar. Methods: The design of this study was quantitative research with a correlational analytical research type through a cross-sectional approach. The sample in this study was 30 nurses using the total sampling method. The instruments in this study were a questionnaire on knowledge about triage and the Triage Skill Questionnaire (TSQ), which were analyzed using the chi square test. Result: The results of the univariate statistical test showed that ER nurse respondents had low knowledge of 86.7%, moderate knowledge of 10% and high knowledge of 3.3%. Meanwhile, nurses who had high skills were 83.3% and moderate skills were 16.7%. Meanwhile, the results of the bivariate statistical test showed that there was a relationship between knowledge and nurses’ skills in implementing triage in the Emergency Room of Labuang Baji Hospital, Makassar with a significance value of p value = 0.002 <0.05. Conclusion: This study found a significant relationship between nurses’ knowledge and their skills in implementing triage in the Emergency Room of Labuang Baji Hospital, Makassar. Improved knowledge contributes to better triage skills, which are crucial in reducing mortality and disability rates while increasing patient satisfaction in emergency care services.